Class Evaluation as an Instrument of Improving the Quality of Education at the Poznań University of Economics - Research, Reflection, and Directions for Change - Wach-Kąkolewicz, Anna (Studia Oeconomica Posnaniensia, 2015)
Ensuring and improving the quality of education, including the quality of academic teaching, is a very important process for the various higher education stakeholder groups, as well as for society as a whole. The importance of the issue of quality has been stressed in a number of documents, particularly in recent years, following the changes that have occurred as a result of university reforms, both at the European (the Bologna Process) and at national or local levels. There is also an ongoing debate on how to improve the quality of education. One of the ways is to take particular care in the evaluation of the educational process, which in most Polish universities comes down to conducting surveys in which students provide feedback on classes and teachers at the end of a semester. Another way of improving the quality of education are class observations, which are usually simply a formal requirement and an unpleasant chore that has to be carried out by superiors rather that an opportunity for supporting the teachers and fostering their professional development. The aim of this paper is to present some possible methods for class evaluation which can promote the development of pedagogical competence and help academics to improve their teaching skills. The issue will be discussed in the broader context of barriers relating to the evaluation of instruction by students.